The Effect of Service Quality, Price, and Product on Purchase Intention - Limanto, Jacqueline Angelica (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
At this time the development of technology is greatly improved. One of the technological developments that is widely used by the public is the internet, with the internet it is very easy for someone's activities, one of which is like shopping activities. Someone can buy what they need without the need to go out of the house, they can buy through Online Store or Online Shop. Indonesia is one of the countries with the development of online shopping sites that are quite rapid, the phenomenon that occurs in online business sales, makes us have to compete in the era of social media by providing advantages to products with quality of service, acceptable prices and surviving in the online market.